Optimal information disclosure strategy in the primary healthcare service market: From the perspective of signaling theory - Liu, Jianyue; Ma, Zhiqiang; Su, Jialu; Ge, Bailin (Frontiers in Public Health, 2022)
The promotion of general practitioner (GP) contract service is one of the key components of China's healthcare reform. We consider GPs providing primary health services with private competency information over two periods, where patients decide when to sign. Two types of GPs are considered: those with higher and lower competency. Under asymmetric information, to spur the patients' incentive to sign, the GPs can move to offer competency disclosure schemes to patients, for example, separating or pooling, through which true competency information is revealed, respectively. We investigate three scenarios, which are referred to as “separating-separating,” “pooling-separating,” and “pooling-pooling.” The results of the three scenarios yield intriguing insights into the impact of the GP's competency disclosure decisions. Findings include that GPs prefer the “pooling-separating” strategy, but patients prefer “separating-separating.” Besides, an extremely low cure rate may enable GPs to conceal some competency information. Furthermore, low-competency GPs may exaggerate their competency level for profit, but greater efforts in disclosing competency information may result in diminished benefits. Therefore, to promote the services of GPs, the core is always to improve GPs' competency.